A motion estimation algorithm for the screen video processing - Druzhinin, D.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2009)
A modification of a motion estimation algorithm for the screen video processing is proposed. This modification works faster than the known similar algorithms. Some results of the comparative testing performed with various algorithms are given. The main distinctions between the screen video and the studio video are discussed.